A brief body scan mindfulness practice has no positive effect on the recovery of heart rate variability and cognitive tasks in female professional basketball players - Aras, Dicle; Samil Onlu, Aysberg; Durmus, Tugay; Cengiz, Caner; Guler, Damla; Guler, Yagmur; Ugurlu, Alkan; Aldhahi, Monira I.; Gülü, Mehmet (Frontiers in Psychology, 2023)
In this study, the acute effects of a short video-based body scan mindfulness practice at the end of the first half of a simulated basketball game on heart rate variability and cognitive task were examined in professional female basketball players. In this crossover randomized controlled trial, nine professional athletes performed the physical loading part consisting of 10-min Yo-Yo Intermittent Recovery Test Level 1 for the first quarter and 10-min basketball game for the second quarter on two different days. Immediately afterwards, they were exposed to a 10-min mindfulness practice or a 10-min nature-based documentary watching as a type of mental intervention. Their HRV, Rating of Perceived Exertion (RPE), National Aeronautics and Space Administration Task Load Index 2 (NASA TLX-2) and Go/No-Go test scores were recorded right before and after the physical loading, and after mental intervention. The physical demand, effort, and frustration level subscales of NASA TLX-2, and the RPE scores were found significantly higher after the physical loading, and they returned to the baseline level after the both types of mental intervention. The Go/No-Go test scores did not differ depending on the measurement time. All time- and frequency-domain heart rate variability parameters except the low-to-high frequency ratio were found significantly high right after the physical loading. Moreover, these parameters were returned to their initial level after both types of mental intervention. Considering the consistency obtained from the measurement tools, it can be stated that the research was successful in creating physical fatigue, but the one-time and short-term mindfulness practice had no additional benefits for the recovery of heart rate variability, cognitive task, and subjective assessment methods such as RPE and NASA TLX-2 in basketball players with no previous experience of mindfulness practice.